Wasp nest-imitated assembly of elastic rGO/p-Ti3C2Tx MXene-cellulose nanofibers for high-performance sodium-ion batteries. (November 2019) - Zhang, Wenjie; Pan, Zheng-Ze; Lv, Wei; Lv, Ruitao; Shen, Wanci; Kang, Feiyu; Yang, Quan-Hong; Weng, Yuqing; Huang, Zheng-Hong
Abstract: Ti3 C2 Tx MXene has drawn considerable attention as anode materials to store sodium ions because of the capability of accommodating the large sodium ions, enabling their intercalation without substantial structural change. However, the limited sodium-ion storage capacity of Ti3 C2 Tx hinders its real application in sodium-ion batteries (SIBs). To enhance its performance as anode materials in SIBs, here, we introduce nanopores into Ti3 C2 Tx sheets by sonication, and after which we assemble them with rGO and cellulose nanofibers into an elastic freestanding composite structure by mimicking the wasp nest. The wasp nest-like structure endows the resulting composite with more accessible surfaces of electrode materials to the electrolyte. Further, the nanopores on the Ti3 C2 Tx sheets and the TiO2 formed from the sonication provide more active sites for sodium storage. As a result, the resulting composite shows a high capacity of 280 mAh g −1 at 100 mA g −1 and remarkable cyclic life with a capacity retention of 84.8% after 1000 cycles at 1 A g −1 . Graphical abstract: Image 1